1994
DOI: 10.1001/archinte.1994.00420230150018
|View full text |Cite
|
Sign up to set email alerts
|

Can Physicians Warn Patients of Potential Side Effects Without Fear of Causing Those Side Effects?

Abstract: Informing patients of potential side effects prior to starting a new medication does not lead to an increased incidence of those side effects. This should not be a reason for physicians to avoid warning patients of potential side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1
4

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 12 publications
0
40
1
4
Order By: Relevance
“…[14] Awareness of medicines risks and experiences of side effects were related in our study, but a number of prospective studies have shown that informing patients about possible ADRs does not lead to their occurrence. [15][16][17] Indeed national guidance on how best to inform patients about side effects has been developed. [18] Most of the patients in our study had been informed about the possibility they had experienced an ADR by a health professional.…”
Section: Comparison To the Literaturementioning
confidence: 99%
“…[14] Awareness of medicines risks and experiences of side effects were related in our study, but a number of prospective studies have shown that informing patients about possible ADRs does not lead to their occurrence. [15][16][17] Indeed national guidance on how best to inform patients about side effects has been developed. [18] Most of the patients in our study had been informed about the possibility they had experienced an ADR by a health professional.…”
Section: Comparison To the Literaturementioning
confidence: 99%
“…Both may lead serious medication errors, potential hospitalization and may compromise the targeted patients' health outcomes. 23 Contrary to the findings of other researchers, 24 the respondent pharmacists may have thought that their discussion of medications' side-effects with patients might trigger patients' fears and/or anxiety, leading to decreased adherence of patients to their prescribed regimens. Patients always demanded thorough information about their medications side-effects and drug-interactions.…”
Section: Discussionmentioning
confidence: 73%
“…Patients always demanded thorough information about their medications side-effects and drug-interactions. 24 As for drug-drug interactions, patients always showed interests in receiving information about them from the dispensing pharmacist. 25 …”
Section: Discussionmentioning
confidence: 99%
“…There were several possible reasons, but, in particular, many physicians were concerned that the power of suggestion might lead some patients, especially suggestible ones, to experience an increase in side effects if they are fully informed about them. 2 Yet, a few studies, conducted to determine whether providing patients with information about potential side effects increases the reported incidence of those side effects, found no relationship between informed consent and side-effect incidence rates.…”
Section: ■■ Informing Patients About Drug Effects Using Positive Suggmentioning
confidence: 99%